Studying the Properties of Porous Alumina Using Starch as a Binder - Alag, Hazim K; Zamel, Rafid Sabbar (Al-Nahrain Journal of Science, 2018)
This work is concerned with the preparation of alumina porous ceramic, the effect of binder (corn starch) and sintered on the physical and mechanical properties of ceramic bodies were. In this work porous raw material ceramic have been produced by using natural additive (corn starch) with (0, 5, 10, 15) wt%. The mixture were dried at 80oC for 2 hours. These samples were sintered at 10000C. Many mechanical properties tests were used to determine the properties of prepared ceramic material which involves: the linear shrinkage, water absorption, apparent porosity, diametrical compression strength, scanning electron microscope (SEM) and x-ray diffraction (X-RD). The results show the interconnected pores between (10-25µm) without additive, (15-28µm) at 5wt%, (17-35µm) at 10wt% and (20-55µm) at 15wt%. The pore size are illustrated by small and large spherical shape the corn starch particle, which are connected and contain an interconnected pores throughout small pores channels.